Consumer Trust In Influencer-Based Digital Marketing: A Qualitative Study Among Beauty Product Consumers In Makassar City - Isma Azis Riu; Irsan Radjab; Hery Maulana Arif; M. Ilham Wardhana Haeruddin; Nurul Fadilah Aswar (PT. Maju Malaqbi Makkarana, 2026)
Influencer marketing has emerged as a dominant strategy within the digital marketing landscape, particularly in the Indonesian beauty industry. This study investigates how consumers in Makassar City develop and sustain trust in influencer-based marketing content on social media platforms. Employing a qualitative descriptive approach, in-depth semi-structured interviews were conducted with 20 purposively selected participants who actively consume beauty content on Instagram, TikTok, and YouTube. Data were analyzed using thematic analysis encompassing open coding, axial coding, and selective coding procedures. The findings reveal five core themes: (1) authenticity as the primary driver of trust formation; (2) the negative impact of excessive commercialization on perceived credibility; (3) the role of influencer expertise and product knowledge in legitimizing recommendations; (4) parasocial relationships as amplifiers of emotional attachment and brand loyalty; and (5) consumer skepticism as an emerging critical evaluation strategy. The study demonstrates that trust remains the central mediating variable linking influencer characteristics to purchase intentions. Consumers exhibit nuanced evaluation behaviors, distinguishing between genuine advocacy and sponsored content. The research contributes theoretically by integrating Source Credibility Theory, Parasocial Interaction Theory, and the Trust-Commitment Theory within the influencer marketing context. Managerially, the findings suggest that brands should prioritize authentic, transparent, and expertise-driven influencer collaborations rather than high-volume promotional campaigns.